PENGGUNAAN MEDIA POHON LITERASI UNTUK MENINGKATKAN MINAT BACA SIAWA KELAS LSD - Hapidah; Wahidah Nasution; Teuku Mahmud (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve the reading interest of first-grade students at SD through the use of the Literacy Tree media in learning activities. The background of this study is based on the low level of students’ reading interest, which is indicated by a lack of enthusiasm in participating in reading activities, minimal interest in reading materials, and a low frequency of students engaging in independent reading. These conditions highlight the need for innovative and engaging learning media that are appropriate to the characteristics of early-grade elementary school students. This research employed Classroom Action Research (CAR), conducted in three cycles. Each cycle consisted of four stages: planning, action, observation, and reflection. The subjects of the study were first-grade students of SD Negeri 61 Banda Aceh. Data were collected through observation sheets, documentation, and reading interest assessment instruments. The Literacy Tree media was used as an attractive visual learning tool designed to display students’ reading outcomes in the form of “literacy leaves” attached to a tree. Each leaf contained simple information such as the book title, short summaries, or students’ impressions after reading. This media aimed to enhance students’ motivation through a visual approach, simple appreciation, and by fostering a sense of pride and confidence in their reading achievements. The results of the study indicate a significant improvement in students’ reading interest in each cycle, as shown by increased participation in reading activities, greater enthusiasm in selecting reading materials, and a higher tendency to engage in independent reading. Therefore, the Literacy Tree media is effective as an alternative learning medium to enhance reading interest among elementary school students.